Inflammation-induced uptake and degradation of the lymphatic endothelial hyaluronan receptor LYVE-1 - Johnson, Louise A; Prevo, Remko; Clasper, Steven; Jackson, David G (The Journal of biological chemistry, 2007)
The hyaluronan receptor LYVE-1 is selectively expressed in the endothelium of lymphatic capillaries, where it has been proposed to function in hyaluronan clearance and hyaluronan-mediated leukocyte adhesion. However, recent studies suggest that hyaluronan homeostasis is unperturbed in LYVE-1(-/-) mice and that lymphatic adhesion/transmigration may be largely mediated by ICAM-1 and VCAM-1 rather than LYVE-1. Here we have explored the possibility that LYVE-1 functions during inflammation and report that the receptor is down-regulated by pro-inflammatory cytokines. Using cultured primary lymphatic endothelial cells, we show that surface expression of LYVE-1 is rapidly and reversibly lost after exposure to tumor necrosis factor-alpha (TNFalpha) and TNFbeta via internalization and degradation of the receptor in lysosomes, coupled with a shutdown in gene expression. Curiously, internalization does not result in significant uptake of hyaluronan, a process that is largely insensitive to the novel LYVE-1 adhesion blocking monoclonal antibody 3A, and proceeds almost equally in resting and inflammation-activated lymphatic endothelial cells. Finally, we show that TNF can induce down-modulation of LYVE-1 in ex vivo murine dermal tissue explants and present evidence that the process occurs in vivo, in the context of murine allergen-induced skin inflammation. These findings suggest that LYVE-1 can function independently of hyaluronan and have implications for the use of LYVE-1 as a histological marker for lymphangiogenesis in human pathology.